Global Variability of Optical Backscattering by Non‐algal particles From a Biogeochemical‐Argo Data Set. Issue 16 (20th August 2019) - Bellacicco, M.; Cornec, M.; Organelli, E.; Brewin, R. J. W.; Neukermans, G.; Volpe, G.; Barbieux, M.; Poteau, A.; Schmechtig, C.; D'Ortenzio, F.; Marullo, S.; Claustre, H.; et al.
Abstract: Understanding spatial and temporal dynamics of non‐algal particles in open ocean is of the utmost importance to improve estimations of carbon export and sequestration. These particles covary with phytoplankton abundance but also accumulate independently of algal dynamics. The latter likely represents an important fraction of organic carbon, but it is largely overlooked. A possible way to study these particles is via their optical backscattering properties (bbp ) and relationship with chlorophyll‐ a (Chl). To this aim, we estimate the fraction of bbp associated with the non‐algal particle portion ( b bp k ) that does not covary with Chl by using a global Biogeochemical‐Argo data set. We quantify the spatial, temporal, and vertical variability of b bp k . In the northern productive areas, b bp k is a small fraction of bbp and shows a clear seasonal cycle. In the Southern Ocean, b k bp is a major fraction of total bbp . In oligotrophic areas, b bp k has a smooth annual cycle. Key Points: The background backscattering of non‐algal particles decrease from Northern to Southern Hemispheres at the surface and in the euphotic layer The background backscattering of NAP has a clear seasonal cycle in the productive areas and a smooth cycle in oligotrophic seas The spatial, temporal, and vertical variability of background backscattering of NAP has to be taken into account in ocean carbon studies